HUBUNGAN PEMBINAAN NASIONALISME TERHADAP KARAKTER KEBANGSAAN SISWA TINGKAT SECONDARY DI SANGKARA SCHOOL BERKURIKULUM INTERNASIONAL - Moria Debora Putri Petra Siahaan; Fazli Rachman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the relationship between fostering nationalism and the national character of students in international standard schools. The research focus was directed at Sangkara School Medan which uses the Cambridge curriculum and has a multicultural learning environment. The phenomenon of low internalization of national character in the midst of globalization is the background for the importance of this study, even though the development of nationalism has been actively implemented by schools through various programs, cultural activities and teacher example. This research uses a correlational quantitative approach with survey methods. The population consisted of secondary level students and sampling was carried out using a cluster random sampling technique, totaling 95 students. Data collection was carried out through distributing questionnaires prepared based on relevant theoretical indicators. These results prove that there is a strong positive relationship between fostering nationalism and students' national character. The conclusion of this research is that the more effective the nationalism development provided by the school, the stronger the students' national character will be formed. This research strengthens the Imagined Communities theory by Benedict Anderson, which states that nationalism is the result of social construction formed through shared experiences, symbols and narratives.